Meningkatkan Kesadaran Peduli Lingkungan Melalui Kegiatan Daur Ulang Sampah Anorganik di Rumah Literasi Ranggi - Diba, Adinda Farah; Hani, Nadia; Darmayana, Zahra; Hairani, Zahra; Rasenda, Rasenda; Sarina, Desi; Suryani, Ruthpani; Yusnadi, Yusnadi; Subaedah, Sitti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to increase environmental awareness through education on cleanliness and recycling at the Ranggi Literacy House located in the PWI Housing Complex Block A59, Jalan PWI, Sampali Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra 20371. The method used in this research is action research with a qualitative approach. The research subjects were 15 children at Ranggi Literacy House, ranging in age from 6 to 12 years old. The research was conducted in several stages, namely planning, action implementation, observation and reflection. Data were collected through direct observation, interviews, documentation of activities, and a simple questionnaire regarding participants' understanding before and after the activity. Furthermore, the data was analysed descriptively qualitatively to see the extent to which this activity can increase environmental awareness among participants. The results of the study showed that after participating in the education, there was an increase in children's understanding of the importance of disposing of waste in its place and skills in recycling waste into more useful items. With the sustainability of this program, it is hoped that environmental awareness can increase and create a culture of caring for the environment among children and the surrounding community.